Coherent leakage of sound from a mixed layer surface duct - Revisited - Jones, A.; Duncan, Alec; Zhang, Z. (2015)
The coherent leakage of a signal from a mixed-layer surface duct with no rough surface scattering is a subject which received considerable attention decades ago. As is well known, coherent leakage of sound from a surface duct reduces progressively as frequency rises from below a nominal trapping frequency to higher values. Considered as modal leakage, or attenuation, the rate of coherent leakage with range for a surface ducted scenario is related to the imaginary part of the horizontal wave number, and may be determined through the use of a modal model of transmission. Such a calculation is performed through an iterative technique, and so when speed is desirable in the calculation, use of a direct analytic expression for leakage would be preferred. To that end, a brief study was made of the suitability of some of the expressions derived originally by Furry and described by Pederson and Gordon (JASA, 47, 304-326, 1970), as the basis for such a determination for the first acoustical mode, in particular. This work includes comparison of leakage rates obtained from expressions based on early work by Furry against results from both the ORCA modal model, and from simulations based on the wave number integration model SCOOTER, for a mixed-layer surface ducted scenario with frequencies relevant to the onset of duct trapping. The work also includes a brief review of some of the early literature relating to leakage of sound from the surface duct.